Dinamika Persahabatan Barnabas dan Paulus - Didik Bagiyowinadi (Seri Filsafat Teologi, 2020)
Barnabas and Paul are the apostles for the Gentiles. Luke does not mention explicitly that both are close friends (philos). This article explores their relationship from the writings of Luke and Paul himself and shows that these apostles who have different backgrounds are not only co-workers or companions in proclaiming gospel. Both have become friends, not because of their quantity of togetherness, but because of the quality of their relationship that marked by mutual belief and support, and one mind-one heart in their joy and suffering in service. Although in the second missionary journey they are separated, the spirit of love is prioritized so that they find the good ending. The dynamic of their friendship would inspire those who are doing the same assignment.